2018
DOI: 10.1016/j.jcin.2018.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ticagrelor, Prasugrel, or Clopidogrel on Endothelial Function and Other Vascular Biomarkers

Abstract: Ticagrelor did not improve endothelial function or increased systemic adenosine plasma levels as compared with prasugrel and clopidogrel in stabilized patients who suffered from an ACS. (Hunting for the Off-Target Properties of Ticagrelor on Endothelial Function in Humans [HI-TECH]; NCT02587260).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 19 publications
1
55
0
1
Order By: Relevance
“…Ticagrelor treatment for 30 days improved endothelial function compared to clopidogrel in patients with a previous ACS and this was correlated to a significant increase in plasma adenosine levels 199 . In contrast, four weeks of treatment with ticagrelor in patients with a previous ACS was not associated with improvement in endothelial function compared to treatment with clopidogrel or prasugrel 200 . Additionally, plasma adenosine levels were unaffected.…”
Section: Effect Of Ticagrelor Treatment On the Endotheliummentioning
confidence: 56%
“…Ticagrelor treatment for 30 days improved endothelial function compared to clopidogrel in patients with a previous ACS and this was correlated to a significant increase in plasma adenosine levels 199 . In contrast, four weeks of treatment with ticagrelor in patients with a previous ACS was not associated with improvement in endothelial function compared to treatment with clopidogrel or prasugrel 200 . Additionally, plasma adenosine levels were unaffected.…”
Section: Effect Of Ticagrelor Treatment On the Endotheliummentioning
confidence: 56%
“…It is possible that these vascular properties of ticagrelor may result in an increased bleeding tendency in the presence of simultaneous inhibition of platelet P2Y 12 . The importance of these effects is uncertain, however, as more recent reports in humans suggest no difference in the vascular effects of thienopyridines and ticagrelor …”
Section: Discussionmentioning
confidence: 99%
“…Ticagrelor had anti-inflammatory effects including reduced formation of platelet-neutrophil aggregates in inflammation models and more profound reduction in Il-6 in a human sepsis model as compared to clopidogrel, suggesting that stronger inhibition of the P2Y12 receptor (ticagrelor) may provide greater anti-inflammatory effect (Nylander and Schulz 2016). Off-target effects of ticagrelor on endothelial function and vascular biomarkers have been speculated on, but a recent study comparing ticagrelor to prasugrel and clopidogrel found no evidence for any non-platelet-mediated effects in post-acute coronary syndrome patients (Ariotti et al 2018).…”
Section: Secondary Prevention Of Atherothrombosis In Patients With Armentioning
confidence: 99%